Critique of Loos’s Anti-Ornament Through Lucretius and Adorno - Levent Şentürk (DEPARCH Journal of Design Planning and Aesthetics Research)
In this article, I will stop by an ancient source, De Rerum Natura, Lucretius’ unaccomplished two-thousand-year-old masterpiece, and try to delve into the centuries-old roots of ornamentation much older than from Gottfried Semper’s Bekleidung (dressing) principle of the nineteenth century. Lucretius’s approach, grounded on Epicurus’ atomism, discloses how nature embellishes and creates existences with this queer principle, starting from atoms, with deviation from end to end. (In the twentieth century, though, we are now aware of the divisibility of atoms and the existence of subatomic particles.) After including these passages, I will try to take a closer look at Adorno’s text, in which he sarcastically states that, the effort to purify has turned into a style itself. After a micro-investigation on the representation of nature, I will conclude my article with a discussion in which I expressed my concerns that the anti-ornamentalism sometimes haunts academic writing under the guise of being scientific.